2009
DOI: 10.4177/ccgp-d-09-00005.1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Drag-Reducing Additives on the Rheological Properties of Fly Ash-Water Suspensions at Varying Temperature Environment

Abstract: A B S T R A C TFly ash transportation and disposal is a major problem in India. Presently fly ash is being transported as lean slurry in pipe lines requiring about 80 to 85% of water which, in turn, consumes more energy input. The objective of the present study is to evaluate the rheological characteristics of fly ash slurry at varying temperatures with and without an additive to facilitate smooth flow in the pipelines. Six fly ash slurry samples were prepared from the fly ash obtained from a thermal power pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…The slope of the line corresponds to the viscosity of the slurry, confirming the slurry as a Newtonian fluid. On the measurement of shear stress, varying the shear rate of the fly ash–water slurry containing different solid weight ratios of fly ash in the presence of 0.017 g/ cc saponin, we have compared the flow characteristic of slurry with CTAB, a commercial dispersant . In the presence of both surfactants, the fly ash–water slurry shows a linear relation between shear stress and shear rate with an early shear yield stress value, indicating a non-Newtonian Bingham plastic fluid in a solid weight fraction range of 50–64%. , The slurry follows the equation of the Bingham plastic model where γ and τ indicate the applied shear rate and shear stress, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The slope of the line corresponds to the viscosity of the slurry, confirming the slurry as a Newtonian fluid. On the measurement of shear stress, varying the shear rate of the fly ash–water slurry containing different solid weight ratios of fly ash in the presence of 0.017 g/ cc saponin, we have compared the flow characteristic of slurry with CTAB, a commercial dispersant . In the presence of both surfactants, the fly ash–water slurry shows a linear relation between shear stress and shear rate with an early shear yield stress value, indicating a non-Newtonian Bingham plastic fluid in a solid weight fraction range of 50–64%. , The slurry follows the equation of the Bingham plastic model where γ and τ indicate the applied shear rate and shear stress, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The reduction of Bingham plastic viscosity, yield stress by using sodium carbonate (0.2% by mass) and Henko detergent (5:1) as an additive in fly ash concentration from 50 to 70% by mass . The outcomes of dispersants such as cetyl trimethyl ammonium bromide (CTAB) and sodium salicylate on stabilization of fly ash slurry in the solid concentration range from 20 to 40% at varying temperatures from 20 to 40 °C reported that the apparent viscosity and shear stress decrease with the increase in temperature even without an additive and the optimized additive concentration in the range of 0.2 to 0.3% by mass. …”
Section: Introductionmentioning
confidence: 99%
“…The lowest viscosity can be obtained at a ratio of larger to fine particle equal to 35:65 (Turian et al 2002 ; Lee et al 2007 ; Barners et al 1989 ; Zhang et al 2011 ; Staroń et al 2013 ). To improve rheological properties of the coal-water suspension, there are used additives, dispersants, such as surfactants and electrolytes (Lee et al 2007 ; Aktas and Woodburn 2000 ; Al-Amrousi et al 1996 ; Seshadri et al 2008 ; Verma et al 2006 ; Naik et al 2009 ; Mukherjee and Pisupati 2016 ; Mosa et al 2008 ; Pat. US4416666 1979 ; Shin and Shen 2006 ; Wu et al 2015 ; Zhang et al 2016 ; Ma et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Naik et al (2009aNaik et al ( , 2009bNaik et al ( , 2011 studied the effects of addition of Cetyl Trimethyl Ammonium Bromide and Sodium Salicylate on the rheological Properties of FA-water suspensions for 20% to 40% concentration at temperature ranging from 20 to 40 0 C and found that the viscosity and shear stress decreased for all the cases with increase in temperature and the slurry without additive showed shear thickening behaviour but exhibited almost Newtonian pattern with a zero yield stress when the concentration of the additive solution increased gradually with an incremental value of 0.1% by mass. According to their investigation the effective additive concentration range was found to be from 0.2% to 0.3% by mass.…”
Section: Literature Reviewmentioning
confidence: 99%